1988
DOI: 10.1007/bf00276849
|View full text |Cite
|
Sign up to set email alerts
|

Insulin as an amyloid-fibril protein at sites of repeated insulin injections in a diabetic patient

Abstract: A patient with Type 1 (insulin-dependent) diabetes mellitus developed localised amyloidosis at the sites of his injections of porcine insulin. A major amyloid fibril protein was extracted and, by means of its amino acid composition and amino acid sequence, it was shown to contain intact insulin molecules. Porcine insulin is the tenth protein and the first foreign protein to be chemically identified in human amyloid fibrils.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
215
1

Year Published

1994
1994
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 288 publications
(219 citation statements)
references
References 12 publications
3
215
1
Order By: Relevance
“…Insulin fibrils pose a variety of problems in biomedical and biotechnological applications. Amyloid deposits of insulin have been observed in patients with diabetes after repeated injection and in normal aging, as well as after subcutaneous insulin infusion (16,17).In our previous work we have shown the important role of partially folded intermediates in insulin fibrillation in vitro (13, 18 -20). In fact, our studies showed that insulin, which is a hexamer at physiological pH, undergoes rapid fibrillation starting at relatively low concentrations of guanidine hydrochloride and urea.…”
mentioning
confidence: 94%
“…Insulin fibrils pose a variety of problems in biomedical and biotechnological applications. Amyloid deposits of insulin have been observed in patients with diabetes after repeated injection and in normal aging, as well as after subcutaneous insulin infusion (16,17).In our previous work we have shown the important role of partially folded intermediates in insulin fibrillation in vitro (13, 18 -20). In fact, our studies showed that insulin, which is a hexamer at physiological pH, undergoes rapid fibrillation starting at relatively low concentrations of guanidine hydrochloride and urea.…”
mentioning
confidence: 94%
“…It has been suggested, however, that its specificity is based on recognition of specific secondary structures rather than specific peptide bonds [16]. It is interesting to note that although the IDE substrates, insulin, atria1 natriuretic peptide and glucagon, are greatly different in primary structure, they probably share a common structural motif allowing them to form amyloid fibrils under certain conditions in vitro [ 171 and in vivo [18,19] been shown to be organized in a cross-j? conformation [ 171.…”
Section: Introdwtionmentioning
confidence: 99%
“…In the late 1960's, the characteristic 4.8 Å cross-␤ x-ray fiber diffraction of pathological amyloid was recognized (4,16), and the cross-␤ structure of insulin fibrils was reported by Burke and Rougvie in 1972 (21). Amyloid deposits containing intact insulin molecules, including the disulfide bridges, have been reported in a patient with insulin-dependent diabetes undergoing treatment by injection of porcine insulin (22). At pH 2, mass spectrometry and hydrogen exchange measurements reveal that insulin forms soluble assemblies of up to 12 molecules in equilibrium with monomers and smaller oligomers (23,24).…”
mentioning
confidence: 99%